2001
DOI: 10.1891/0886-6708.16.2.127
|View full text |Cite
|
Sign up to set email alerts
|

Dropout and Completion of Treatment Among Spouse Abusers

Abstract: This study examines a population of spouse abusers undertaking a treatment program. Its purpose was to identify the variables associated with dropout and completion of treatment and to build a predictive model. Data were collected on 286 men who began group treatment in one of eight community programs in the province of Quebec, Canada. Results show that men who complete treatment are older, better educated and have better economic conditions than men who drop out. They also have a more stable family life, have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
39
0
12

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 0 publications
2
39
0
12
Order By: Relevance
“…Working alliance has been found to predict treatment completion in a battering population (Rondeau, Brodeur, Brochu, & Lemire, 2001) as well as a reduction in psychological and physical aggression at follow-up (Taft, Murphy, King, Musser, & DeDeyn, 2003). In fact, Taft et al (2003) found that therapists' ratings of working alliance were the strongest predictors of outcome.…”
Section: Working Alliance and Group Cohesion As Indicators Of Treatmementioning
confidence: 99%
“…Working alliance has been found to predict treatment completion in a battering population (Rondeau, Brodeur, Brochu, & Lemire, 2001) as well as a reduction in psychological and physical aggression at follow-up (Taft, Murphy, King, Musser, & DeDeyn, 2003). In fact, Taft et al (2003) found that therapists' ratings of working alliance were the strongest predictors of outcome.…”
Section: Working Alliance and Group Cohesion As Indicators Of Treatmementioning
confidence: 99%
“…En raison de l'ampleur de ce phénomène d'attrition et de son importance pressentie, certains chercheurs ont tenté de mettre à jour les déterminants et les prédicteurs de l'abandon au sein des programmes de thérapie pour hommes violents. Les principales variables prédictrices qui ont été étudiées sont reliées aux caractéristiques personnelles et socio-démographiques des clients et des programmes de traitement euxmêmes (Cadsky et al, 1996 ;Gondolf, 1990 ;Rondeau et al, 2001). Dans leurs études portant sur les variables-client, plusieurs chercheurs ont découvert que les hommes qui abandonnent la thérapie en cours de processus sont en général plus jeunes que ceux qui terminent le traitement (Rondeau et al, 2001 ;DeMaris et al, 1989 ;Saunders et Parker, 1989).…”
unclassified
“…Les principales variables prédictrices qui ont été étudiées sont reliées aux caractéristiques personnelles et socio-démographiques des clients et des programmes de traitement euxmêmes (Cadsky et al, 1996 ;Gondolf, 1990 ;Rondeau et al, 2001). Dans leurs études portant sur les variables-client, plusieurs chercheurs ont découvert que les hommes qui abandonnent la thérapie en cours de processus sont en général plus jeunes que ceux qui terminent le traitement (Rondeau et al, 2001 ;DeMaris et al, 1989 ;Saunders et Parker, 1989). Les clients qui ne persévèrent pas diffèrent également de ceux qui complètent le traitement de la façon suivante : ces derniers sont plus souvent mandatés par la cour (condition imposée lors d'une sentence) ; la participation et la collaboration sont donc souvent moindres lorsque les clients consultent sur une base volontaire.…”
unclassified
See 2 more Smart Citations